Focal group as a research tool in health - Ferrazza, Cristine Aspirot do Couto; Colomé, Juliana Silveira (Disciplinarum Scientia | Saúde, 2021)
Introduction: The “focus group” methodology, developed by Social Sciences, has been successfully applied to qualitative research in health. Aim: The present study was carried out through an integrative literature review, in order to collect data about this methodology over health practice. Methodology: After a detailed revision following previous determined criteria, twelve studies, within a 20-year time range, were selected on the Virtual Health Library (VHL) and Google Scholar databases. Results and Conclusion: From the analyzed authors, it was possible to state that the focus group methodology, instrumentalized through group meetings composed of around twelve people and a moderator helping and guiding to predetermined topics, has great potential for collecting data in qualitative research, for providing the debate and collective stimulus to the expression of opinions and perceptions that would not appear in individual interviews. Additionally, it was found that the Strategic Focal Analysis, using the techniques of the Focal Group over the external and internal environment analysis, originating from the Strategic Planning area, also has the potential to be a management tool, especially to strategic planning over health service. More studies are required to stablish methodological tools.